SISTEM INVENTORI DAN PENJUALAN BERBASIS WEB DAN ANDROID PADA TOKO CAHAYA ARLOJI MENGGUNAKAN KONSEP 7C FRAMEWORK - Andrew Jhosua; Desi Arisandi; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
Web and Android-based Inventory and Sales Systems at Cahaya Arloji stores using the 7C Framework concept is an application that aims to assist the process selling and product record. The application is used by owners and staff to manage Cahaya Arloji stores online, while for cutomers is used to see any  products are being sold at Cahaya Arloji stores, and help to make online order. Application designed using the PHP and Android programming languages. The application design method is using the System Development Life Cycle and where using the Waterfall model. The results of the tests were tested using User Acceptance Test method and user self-satisfaction using a questionnaire. With this application, it can helping the process of record buying and selling at Cahaya Arloji stores